Adsorption behavior of methacryloyloxydecyl dihydrogen phosphate on an apatite surface at neutral pH. (2nd March 2016) - Bista, Baba; Nakashima, Syozi; Nikaido, Toru; Sadr, Alireza; Takagaki, Tomohiro; Romero, Maria J. R. H.; Sato, Takaaki; Tagami, Junji
Abstract : This study aimed to quantify the adsorption affinity of neutralized 10‐methacryloyloxydecyl dihydrogen phosphate (10‐MDP‐N) toward hydroxyapatite (HA) and dicalcium phosphate dihydrate (DCPD) at pH 7.0 by employing the Langmuir isotherm model. Furthermore, the effects of inorganic phosphate (Pi) and fluoride (F − ) ions on the adsorption of 10‐MDP‐N onto HA and DCPD were examined. Fixed amounts of HA and DCPD powders were suspended in different concentrations of 10‐MDP‐N solutions and were incubated for 18 h. Equilibrated concentrations of 10‐MDP‐N were measured by spectrophotometry and the adsorption affinity was estimated using the Langmuir model. Moreover, the adsorption was examined by zeta‐potential analysis. The results indicated that significant Langmuir correlation was noted in both substrates, along with an increasing negative zeta‐potential; however, in DCPD the correlation was less strong. The addition of 1.0 mM Pi slightly delayed the adsorption of 10‐MDP‐N onto both substrates, whereas 3.0 mM Pi drastically delayed adsorption onto HA but completely inhibited adsorption onto DCPD. Up to 50 ppm, F − enhanced the adsorption onto HA, and the adsorption plateaued at higher concentrations of F −, whereas no obvious influence of F − on the adsorption onto DCPD was noted.